PEMANFAATAN WEBSITE SEBAGAI SISTEM INFORMASI UNTUK MANAJEMEN PERSEDIAAN BARANG PADA TOKO X - Febryantahanuji Febryantahanuji; Triyani Triyani; Arsito Ari Kuncoro (Elkom : Jurnal Elektronika dan Komputer, 2019)
In today's industry competition the use of a technology is very important, including in inventory management. This system is used to enter inventory data into the database so that there are no errors in the report. So that in it often occurs stock report errors in the availability of goods that result in data not being updated, the system that will be created by the author is a system of inventory information that is useful to overcome these problems. This system is also equipped with reports on incoming and outgoing goods data reports, minimum and maximum stock reports, and Web-based stock data reports. With this inventory information system, it is expected to be able to help the existing problems, facilitate data collection, the system built can provide access rights for each user, as well as facilitate the preparation of reports so that the Program is able to handle existing problems.